Application of neoadjuvant chemotherapy in occult breast cancer: Five case reports. Issue 40 (October 2017) - Yang, Haisong; Li, Ling; Zhang, Mengmeng; Zhang, Shiyong; Xu, Shu; Ma, Xiaoxia
Abstract: Rationale: Although rare, occult breast cancer (OBC) originates from breast tissue. Its primary lesions cannot be identified by clinical examination or imaging; therefore, the diagnosis, treatment, and prognosis remain controversial. Patient concerns: This study comprised 5 female OBC patients who were admitted to the Affiliated Hospital of Guizhou Medical University for painless axillary lumps. Diagnoses: 18 F-flurodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) indicated metastasis in the ipsilateral axillary lymph nodes. No clear breast primary lesions were identified; other organs were also excluded as the primary site. Pathological biopsy confirmed axillary lymph node metastasis of adenocarcinoma. Immunohistochemical staining of the tumor to identify the source revealed that estrogen receptors (ERs) and progesterone receptors (PgRs) were positive in 2 cases, ER was positive and PR was negative in 1 case, and both were negative in 2 cases. Human epidermal growth factor receptor 2 was negative in all cases. All patients were diagnosed with OBC. Interventions: All patients underwent neoadjuvant chemotherapy (NAC). One patient did not undergo follow-up therapy. The other 4 underwent total mastectomy plus axillary lymph node dissection followed by radiotherapy. Two patients also underwent endocrine therapy. Outcomes: Patients were followed up for 9.0 to 72.0 months. Four achieved pathological complete response. One patient experienced metastasis to the ipsilateral supraclavicular lymph nodes 2.0 years later, which was cleared after additional treatment. The other patients were tumor free. Lessons: Here, we are reporting 5 cases of OBC treated with NAC that were evaluated by 18 F-FDG PET/CT scans. This study suggests that NAC might lead to a positive outcome.